"It has changed my whole life": The systemic implications of chronic low back pain among older adults. Issue 2 (17th February 2018) - Stensland, Meredith L.; Sanders, Sara
ABSTRACT: Chronic low back pain (CLBP) is the most common pain complaint among older adults. Despite its prevalence, very little research has qualitatively examined the diverse consequences of living with CLBP in later life. As part of a larger study aiming to understand the experience of CLBP among older adults, the objective of this manuscript is to understand how older adults experience CLBP and its impacts on the functioning of older adults. Guided by van Manen's phenomenological method, 23 semi-structured interviews with 21 pain clinic patients aged 66–83 were conducted. Through an iterative process assisted by NVivo 11 software, researchers used line-by-line thematic coding to identify main impacts of CLBP. Under the main theme "It has changed my whole life, " results are reflected in six subthemes: (a) Pain damages sense of self; (b) trapped in a body that doesn't work anymore; (c) me, my partner, and my pain; (d) pain complicates family relationships; (e) painfully employed; and (f) feeling socially and recreationally repressed. This study improves our understanding of older pain clinic patients' experience of living with debilitating CLBP and offers direction for social work intervention in the context of multidisciplinary pain management.